Dampak Partisipasi PT. Tanito Harum Dalam Pembangunan Fisik Jalan Pada Kesejahteraan Sosial Masyarakat Di Kelurahan Loa Tebu Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Umar, Nasir (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
ABSTRAK Tanito Harum, Incorporated is a national coal mining company , which located and having area territory in Loa Tebu, Tenggarong City, Kutai Kartanegara Regency which has been operated since 1980. As one of national coal mining company which is big enough , where the territory and location / its area located in kabupaten Kutai Kartanegara area, definitely this national coal mining company have consequence and responsibility to the society surroundings. Because commonly that coal mining company is not only orientate to the profit itself, but also to build, to effort, and to prosper the society, bring the change to the society surroundings.